Menyinergikan Kecerdasan Spiritual, Emosional, dan Intelektual Melalui Perspektif Al-Qur’an - Albar, Kholid; Harun, Hamzah; Latif, Muhaemin (Jurnal Keislaman, 2024)
This article discusses the importance of synergizing the three types of human intelligence, namely spiritual, emotional and intellectual intelligence, through the perspective of revelation. According to the Quran, humans were created with hearing, sight and conscience as a means to understand and manage themselves in a balanced manner. Spiritual intelligence is related to the human ability to establish a close relationship with the Creator, emotional intelligence is related to the ability to manage emotions and empathize, and intellectual intelligence is related to the ability to think critically, creatively, and innovatively. The research approach in this study will use a qualitative approach with a library research method. Where this research wants to explore and understand the concept and perspective of revelation in synergizing spiritual, emotional, and intellectual intelligence. The data analysis technique in this research is content analysis where the process is to analyze the content and meaning of the data sources collected, then interpretation and synthesis, namely by understanding, interpreting, and synthesizing information from various sources to build a comprehensive understanding. The results show that the current phenomenon shows that many people only develop one aspect of intelligence, resulting in an imbalance. Individuals who only focus on developing intellectual intelligence tend to become rigid, self-centered, and insensitive. Conversely, individuals who only develop spiritual and emotional intelligence tend to be less able to think critically and face life's challenges effectively. Therefore, this article emphasizes the importance of synergizing the three aspects of intelligence through the perspective of revelation so that humans can achieve true blessings and happiness in life and carry out their functions and responsibilities as caliphs on earth.